DIAGNOSING STUDENTS’ MISCONCEPTIONS IN CHEMICAL EQUILIBRIUM THROUGH A THREE-TIER MULTIPLE CHOICE APPROACH - Raehanah Raehanah; Nurul Askin (UIN Mataram, 2026)
This study aimed to identify students' misconceptions about chemical equilibrium using the Three Tier Multiple Choice (TTMC) diagnostic instrument and to analyze them based on multiple chemical representations. A quantitative descriptive design was employed involving 78 eleventh-grade students of SMAN 1 Pringgarata selected through total sampling. The research instrument was a TTMC test consisting of three tiers: answer, reason, and confidence level, enabling a more accurate diagnosis of students' conceptual understanding. Data were analyzed using descriptive quantitative methods. The results revealed that misconceptions across the assessed indicators ranged from 32.05% to 48.07%, with an overall misconception rate of 42%, categorized as moderate. Based on the analysis of multiple chemical representations, the highest misconception occurred in the macroscopic representation (44.2%), followed by the symbolic representation (43.6%) and the submicroscopic representation (37.2%). These findings indicate that students still experience difficulties integrating macroscopic phenomena, submicroscopic particle behavior, and symbolic representations when understanding chemical equilibrium concepts. The TTMC instrument proved effective for diagnosing students' misconceptions and can serve as a basis for designing chemistry instruction that explicitly integrates the three levels of chemical representation. ABSTRAK Penelitian ini bertujuan mengidentifikasi miskonsepsi siswa pada materi kesetimbangan kimia menggunakan instrumen Three-Tier Multiple Choice (TTMC) serta menganalisisnya berdasarkan multiple chemical representations. Penelitian menggunakan pendekatan deskriptif kuantitatif dengan subjek 78 siswa kelas XI SMAN 1 Pringgarata yang dipilih menggunakan teknik sampling jenuh. Instrumen penelitian berupa tes TTMC yang terdiri atas tiga tingkat, yaitu jawaban, alasan, dan tingkat keyakinan, sehingga mampu mengidentifikasi pemahaman konseptual siswa secara mendalam. Data dianalisis secara deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa persentase miskonsepsi pada setiap indikator berkisar antara 32,05%–48,07%, dengan persentase miskonsepsi keseluruhan sebesar 42% yang termasuk kategori sedang. Berdasarkan analisis multiple chemical representations, miskonsepsi tertinggi ditemukan pada representasi makroskopik (44,2%), diikuti oleh representasi simbolik (43,6%), dan submikroskopik (37,2%). Temuan ini menunjukkan bahwa siswa masih mengalami kesulitan mengintegrasikan fenomena makroskopik, mekanisme partikel pada tingkat submikroskopik, dan representasi simbolik dalam memahami konsep kesetimbangan kimia. Instrumen TTMC efektif digunakan sebagai alat diagnostik untuk mengidentifikasi karakteristik miskonsepsi siswa dan dapat menjadi dasar dalam merancang pembelajaran kimia yang mengintegrasikan ketiga representasi tersebut.